Baseline Practices for the Application of Genomic Data Supporting Regulatory Food Safety. (22nd November 2019) - Lambert, Dominic; Pightling, Arthur; Griffiths, Emma; Van Domselaar, Gary; Evans, Peter; Berthelet, Sharon; Craig, Duncan; Chandry, P Scott; Stones, Robert; Brinkman, Fiona; Angers-Loustau, Alexandre; Kreysa, Joachim; et al.
Abstract: The application of new data streams generated from next-generation sequencing (NGS) has been demonstrated for food microbiology, pathogen identification, and illness outbreak detection. The establishment of best practices for data integrity, reproducibility, and traceability will ensure reliable, auditable, and transparent processes underlying food microbiology risk management decisions. We outline general principles to guide the use of NGS data in support of microbiological food safety. Regulatory authorities across intra- and internationaljurisdictions can leverage this effort to promote the reliability, consistency, and transparency of processes used in the derivation of genomic information for regulatory food safety purposes, and to facilitate interactions and the transfer of information in the interest of public health.